Effluent quality of wet process coffee processing factories in coffee growing ecological zones in Burundi - Bisekwa, E.; Njogu, P.M.; Kufa-Obso, T. (Sci Forschen, Inc., 2020)
Arabica coffee is cultivated by smallholders for commercial purposes, and it is commonly processed using wet Coffee Processing Technology. Burundi has more than 250 Coffee Processing factories which discharge their effluents to water bodies. The goal of this study was to determine the levels of physicochemical parameters in wastewater from Coffee Processing Technology factories in major coffee growing ecological zones in Burundi. Wastewater samples were collected from 19 sites representing private, public and cooperative owned coffee processing stations. Physicochemical analyses were determined in-situ field and laboratory conditions using standard procedures. Results indicate that the wastewater does not meet Burundi Effluent Discharge standards for Total Suspended solids, Chemical Oxygen Demand, Biochemical Oxygen Demand, pH. The data revealed that the wet coffee processing pollutes the environment in terms of pH, Total Suspended solids, Chemical Oxygen Demand, Biochemical Oxygen Demand. There is need to install quality polishing technologies to treat the water before disposal.